Peran Kepuasan Mahasiswa dalam Memediasi Pengaruh Kualitas Layanan, Citra Perguruan Tinggi, dan Experiential Marketing Terhadap Keunggulan Bersaing Perguruan Tinggi Swasta : (Studi Empiris pada Universitas di Kabupaten Kuningan) - Rodhiyah, Rodhiyah; Edy Suroso; Ade Komaludin (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study aims to examined the direct and indirect influence of service quality, university image and experiential marketing on the competitive advantage of private universities with student satisfaction as a mediation variable. Empirical studied were conducted at private universities in Kuningan Regency. Sampling was carried out used proportionate stratisfied random sampling techniques with a total sample of 380 samples who were active students with minimum criteria for have taken lectures for one year. The instrument of this study is a statement questionnaire with Likert scale. Data analysis techniques used Stuctural Equation Modelling with Smart PLS applications. The results showed 1) Service quality, university image, experiential marketing and student satisfaction are in good criteria while competitive advantage is in very good criteria. 2) The quality of service and university image have a positive and significant effect on competitive advantage, but experiential marketing have a negative and insignificant effect on competitive advantage 3) Quality of service, university image and experiential marketing have a positive and significant effect on student satisfaction 4) Student satisfaction has a positive and significant effect on competitive advantage 5) Quality of service, university image and experiential marketing have a positive and significant effect on competitive advantage through student satisfaction as a mediation variable. 6) In multigroup analysis, the role of satisfaction in mediating the influence of service quality, university image and experiential marketing on competitive advantage at the two universities there is no significant difference.